Pengaruh Suhu Dan Variasi Rasio Plastik Jenis Polypropylene Dan Plastik Polytyrene Terhadap Yield Dengan Proses Pirolisis - Ricki Gunawan; Syarfi Daud; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Increased plastic waste has a negative impact on the environment if not further processed, Because plastic waste is nonbiodegradable One method that can be used to process plastic waste is pyrolysis method.The purpose of this study was to observe the effect of process variables (temperature and ratio of PP plastic: PS) to yield and characterization of pyrolysed oil produced. the pyrolysis process is carried out at temperature variations of 300 ° C, 350 ° C, and 400 ° C. And variation of PP plastic ratio: PS 100: 0, 80:20, 60:40 and 50:50 hours 120 minutes And active clay catalyst 1.5% of the raw material. The highest yield was 68.87% at 400 ° C and variation of PP: PS 50:50. Characterization of pyrolysis oil obtained in the form of density 0,761 gr / ml, kinematic viscosity 2,961 cSt, flash point 38oC and calorific value 44,673 MJ / kg are in the range of diesel spesifications.Keywords : active clay , Pyrolysis, polypropylene, polystyrene, , pirolitic oil